Cyber Law and Islamic Family Law: Safeguarding Women’s and Children’s Rights in the Digital World - Muyassar, Ya’ Rakha; Dawi, Klara; Muhayan; Sitorus, Angelia Pratiwi Mastiurlani Christina; Setiawan, Agus (Arus Jurnal Sosial dan Humaniora, 2024)
This research explores a crucial topic amidst the evolving digital era of this decade, particularly concerning the protection of women's and children's rights, with a focus on the intersection of Islamic family law and cyber law. With rapid technological advancements, it is essential to analyze the legal frameworks within Islamic family law and cyber law that safeguard the rights of women and children. This stems from the myriad legal issues arising in tandem with the progress of time, such as online infidelity, marriage and divorce conducted via teleconferences, digital security between spouses, and children's privacy in the digital world. This study delves into the challenges and opportunities emerging in the digital era, providing valuable insights into the continuously evolving landscape of legal protection. By examining the perspectives of Islamic family law alongside cyber law, this research offers a comprehensive understanding of contemporary complex issues prevalent in this decade. The findings provide insights into the necessary steps to ensure adequate protection of women's and children's rights in the ever-changing digital world, emphasizing the importance of harmonious integration between Islamic legal principles and contemporary cyber regulations. Therefore, this research aims to formulate responsive and effective policies to address challenges in the current digital landscape, enabling adaptability to the evolving times.